Medicine and kindness, a glorious concurrence? - Araya Gautam (Patient Experience Journal, 2023)
This article unfolds the journey of a 28-year-old junior doctor entangled in the throes of a pernicious anemia diagnosis during her travels abroad, a scenario exacerbated by the grip of a COVID-19 lockdown. Adrift without medical insurance and distant from her family, she found herself under the care of a compassionate on-call resident, emphasizing the crucial role of kindness and compassion in her predicament. Her treatment regimen encompassed a series of CBC tests meticulously tracking cobalamin and ferritin levels, complemented by extensive examinations for iron deficiency and a regimen of vital vitamin B12 injections, all carried out under vigilant scrutiny to ensure the eventual normalization of her lab findings—a process spanning over a week. As the medical landscape continues to grapple with the COVID-19 pandemic, stories like hers underscore the vital need for empathy and understanding within the healthcare sphere. In these challenging times, compassion emerged as a lifeline, bridging the gap between distress and recovery. This narrative serves as a poignant reminder that amidst the complexity of medical science, it is often the simplest acts of kindness that can make all the difference. In the face of an ongoing shift towards policy-centric healthcare, the article advocates a return to a patient-centric approach, one where kindness becomes an integral element of treatment, alleviating anxiety, reducing uncertainty, and promoting overall well-being. It prompts readers to reflect on the profound impact of compassion and empathy in medicine, sparking a dialogue on how fostering a more humane and inclusive healthcare system ultimately benefits us all. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.